Manajemen Pembelajaran Nilai Karakter Kerjasama Melalui Permainan Batu Kerikil di TK Kemala Bhayangkari 31 Tanggul - Fitri Nur Aini; Asri Widiatsih; Pipit Rika Wijaya (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This research explores the use of the traditional batu kerikil (bakil) game as a means to foster cooperative character values among young children at TK Kemala Bhayangkari 31 Tanggul. Beyond its role as entertainment, traditional games function as educational tools that help instill social values such as teamwork, empathy, and responsibility. Initial observations indicated that several children still faced challenges in collaborating during group activities. Adopting a descriptive qualitative method, data were collected through observations, interviews, and documentation. The participants included one classroom teacher and ten Group A students. Data analysis followed Miles and Huberman’s stages of reduction, display, and conclusion drawing. The results are expected to offer insights into effective learning management strategies for nurturing cooperative character through the bakil game and to support the advancement of culture-based learning approaches in early childhood education.